A framework for considering the utility of models when facing tough decisions in public health: a guideline for policy-makers - Jason Thompson; Roderick McClure; Nick Scott; Margaret Hellard; Romesh Abeysuriya; Rajith Vidanaarachchi; John Thwaites; Jeffrey V. Lazarus; John Lavis; Susan Michie; Chris Bullen; Mikhail Prokopenko; et al. (BMC, 2022)
Abstract The COVID-19 pandemic has brought the combined disciplines of public health, infectious disease and policy modelling squarely into the spotlight. Never before have decisions regarding public health measures and their impacts been such a topic of international deliberation, from the level of individuals and communities through to global leaders. Nor have models-developed at rapid pace and often in the absence of complete information-ever been so central to the decision-making process. However, after nearly 3 years of experience with modelling, policy-makers need to be more confident about which models will be most helpful to support them when taking public health decisions, and modellers need to better understand the factors that will lead to successful model adoption and utilization. We present a three-stage framework for achieving these ends.